DETERMINATION OF EFFECTIVE DOSE OF ANTIMALARIAL FROM CASSIA SPECTABILIS LEAF ETHANOL EXTRACT IN PLASMODIUM BERGHEI-INFECTED MICE - Ekasari, Wiwied; Wahyuni, Tutik Sri; Arwaty, Heny; Putri, Nindya T. (African Journal of Infectious Diseases (AJID), 2018)
Background: The preliminary study on antimalarial activity of the ethanol extract of Cassia spectabilis leaves against Plasmodium berghei has been carried out by in vivo experiment. It was demonstrated that ethanol extract of C. spectabilis leaves could inhibit growth of rodent malaria parasite P. berghei by 59.29 % (at a dose of 100 mg/kg bodyweight). However, further investigation is required to determine an effective dose of the administered extract for a higher inhibitory effect and increasing effectiveness of the extract.Material and Methods: To determine the effective dose of ethanol extract of C. spectabilis leaves, a "4-day suppressive test"of Peter was performed with some modifications. The extract was administered orally to P. berghei-infected mice in multiple doses (twice and thrice daily) and single dose (once daily) with dose ranging from 50 - 250 mg/kg body weight. Antimalarial activities were determined by analyzing suppression of parasitaemia of treated mice.Results: The results showed that oral administration of the ethanol extract of C. spectabilis leaves at dose of 150mg/kg bodyweight thrice daily possessed higher inhibition (62.42%) compared to those twice daily (52.58%) and once daily (46.25%).Conclusion: These results suggested that ethanol extract of C. spectabilis is promising candidate for development of antimalarial drugs. The effective dose of the ethanol extract is 150 mg/kg bodyweight with thrice administration daily.